2021
DOI: 10.3168/jds.2020-18950
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet fermentability and supplementation of 2-hydroxy-4-(methylthio)-butanoic acid and isoacids on milk fat depression: 2. Ruminal fermentation, fatty acid, and bacterial community structure

Abstract: The experiment was conducted to understand ruminal effects of diet modification during moderate milk fat depression (MFD) and ruminal effects of 2-hydroxy-4-(methylthio)-butanoic acid (HMTBa) and isoacids on alleviating MFD. Five ruminally cannulated cows were used in a 5 × 5 Latin square design with the following 5 dietary treatments (dry matter basis): a high-forage and low-starch control diet with 1.5% safflower oil (HF-C); a low-forage and high-starch control diet with 1.5% safflower oil (LF-C); the LF-C d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 56 publications
1
11
1
Order By: Relevance
“…The average ASV that were observed (n = 1,308) or derived by the Chao 1 nonparametric statistic (n = 1,392) indicate a robust prokaryotic community. Although we noted no change in our study resulting from dosing BCVFA, when BCVFA were fed to lactating dairy cattle, the number of ASV and most indices of α-diversity increased (Lee et al, 2021). Our β-diversity results (Figure 1) support the major shifts in relative ASV abundance associated with pH, and the period effect reflects the important role of differing inocula sources.…”
Section: Relative Sequence Abundance Of Prokaryotessupporting
confidence: 44%
See 2 more Smart Citations
“…The average ASV that were observed (n = 1,308) or derived by the Chao 1 nonparametric statistic (n = 1,392) indicate a robust prokaryotic community. Although we noted no change in our study resulting from dosing BCVFA, when BCVFA were fed to lactating dairy cattle, the number of ASV and most indices of α-diversity increased (Lee et al, 2021). Our β-diversity results (Figure 1) support the major shifts in relative ASV abundance associated with pH, and the period effect reflects the important role of differing inocula sources.…”
Section: Relative Sequence Abundance Of Prokaryotessupporting
confidence: 44%
“…Following thawing, DNA was extracted and purified (Wenner et al, 2020) before sequencing of the 16S rRNA gene. Computational procedures were as described by Lee et al (2021). Briefly, the Illumina MiSeq 2 × 300 pairedend protocol was used, followed by filtering, annotation, and cluster analysis using amplicon sequencing variants (ASV) clustered at 99% similarity.…”
Section: Continuous Culture Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have also shown that C. butyricum can regulate the relative abundance of intestinal flora, consolidate intestinal barrier function and accelerate metabolism, to improve bodily health and immunity ( 12 , 15 , 16 ). In addition, its metabolite butyrate and other substances are also widely used in animal production to improve the performance of livestock and poultry, including improving the rumen fermentation of ruminants, and regulating rumen flora ( 17 , 18 ). High-concentrate diets in production can provide higher energy in the short term for increasing ruminant growth rates.…”
Section: Introductionmentioning
confidence: 99%
“…Amplicon libraries were pooled and sequenced (2 × 300 bp paired-end sequencing) using the MiSeq platform (Illumina Inc.). Quality control (denoising, merging, removal of chimeras) was applied through QIIME2 (version 2019.10; Bolyen et al, 2019), similarly to Lee et al (2021). The final quantity of quality amplicon sequencing variants (ASV) used in this analysis numbered 3,855,702 and were clustered into taxonomy based on 99% similarity using the Silva 16S reference database (NR 132 version; Quast et al, 2013).…”
Section: Effect Of Zinc Source (Zinc Sulfate or Zinc Hydroxychloride)...mentioning
confidence: 99%